Changes in Production Modes and Intellectual Relations in Managing the Behavior of Oil and Gas Labors in Muara Badak District: Perubahan Mode Produksi dan Relasi Intelektual Dalam Pengaturan Prilaku Buruh Migas di Kecamatan Muara Badak - Priambodo, Nalendro; Murlianti, Sri; Nanang, Martinus (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
ABSTRACT: This study aims to identify the pattern of changes in the mode of production of people who work as farmers and fishermen in Kutai Kartanegara Regency, especially Muara Badak District after the entry of the oil and gas industry in the region, and analyze how intellectual relations are in regulating the behavior of oil and gas workers along with the social, economic and political impacts. raised. This type of qualitative research uses the Grounded Theory approach. The results of this study indicate that changes in the way people produce from agriculture, plantations, and traditional fisheries in Muara Badak District have been accompanied by a mechanism for releasing social ties to land and sea through intermediary policies that are pro to the formation of industrial commodities for market interests and result in a decline in the domestic industry due to dependence. in the oil and gas industry. This dependence also gave birth to an intellectual layer and a working class that served the interests of the plantation, aquaculture and oil and gas-based industries. The process of its journey was accompanied by the emergence of various kinds of class conflicts, which gave rise to types of organic intellectuals who tried to fight back against the exploitation that occurred. ABSTRAK: Penelitian ini bertujuan untuk mengindentifikasikan pola perubahan mode produksi masyarakat yang berprofesi sebagai petani dan nelayan di Kabupaten Kutai Kartanegara, khususnya Kecamatan Muara Badak setelah masuknya industri migas di wilayah tersebut dan menganalisis bagaimana relasi intelektual dalam pengaturan prilaku buruh migas beserta dampak sosial, ekonomi dan politik yang ditimbulkan. Jenis penelitian kualitatif dengan menggunakan pendekatan Grounded Theory. Hasil penelitian ini menunjukan bahwa perubahan cara masyarakat berproduksi dari pertanian, perkebunan dan perikanan tradisional di Kecamatan Muara Badak ikut dibarengi dengan mekanisme pelepasan ikatan sosial dengan tanah dan laut melalui perantara kebijakan yang pro terhadap pembentukan komoditas industri untuk kepentingan pasar serta mengakibatkan kemunduran industri domestik akibat ketergantungan pada industri migas. Ketergantungan ini juga melahirkan lapisan intelektual dan kelas buruh yang mengabdi pada kepentingan industri berbasis perkebunan, pertambakan dan migas. Dalam proses perjalalanannya juga dibarengi dengan kemunculan berbagai macam konflik kelas sehingga memunculkan jenis intelektual organik yang berusaha melakukan perlawanan balik terhadap eksploitasi yang terjadi.